How to do everything iPad 2 - Ballew, Joli. (New York : McGraw-Hill, 2011)
'Get the most out of your iPad 2!How to Do Everything: iPad 2 shows you how to quickly master the basics of the iPad 2, including sending/receiving SMS messages and e-mail, surfing the Internet, reading e-books and other online content, and customizing the iPad 2. Chapters progress to more complex tasks such as taking/sending images and video, using the forward- and rear-facing cameras to video chat, plus getting content from the App Store and iTunes. This step-by-step guide explains how to do a myriad of interesting things: map routes with the built-in GPS, sync your iPad 2 with your computer, rent movies, take handwritten notes and translate them into typed pages, and more. How to Do Everything: iPad 2 shows you how to: Personalize your iPad 2 with applications, ringtones, themes, skins, wallpapers, and accessories Download and access e-books, online newspapers, magazines, videos, movies, blogs, journals, and educational materials, such as college textbooks and lab manuals Place and answer phone calls, use voice activation, add contacts, and incorporate a Bluetooth headset Send and receive text, picture, video, and e-mail messages Use the forward- and rear-facing cameras that enable video chat Find Wi-Fi hotspots, surf the Internet, and explore GPS and maps Connect the iPad 2 to home entertainment centers or game consoles'--
Includes index.
Keywords: iPad (Computer).; Tablet computers